Evaluation of Carbapenemase Screening and Confirmation Tests with Enterobacteriaceae and Development of a Practical Diagnostic Algorithm - Maurer, Florian P. (J Clin Microbiol, 2014)
Reliable identification of carbapenemase-producing members of the family Enterobacteriaceae is necessary to limit their spread. This study aimed to develop a diagnostic flow chart using phenotypic screening and confirmation tests that is suitable for implementation in different types of clinical laboratories. A total of 334 clinical Enterobacteriaceae isolates genetically characterized with respect to carbapenemase, extended-spectrum β-lactamase (ESBL), and AmpC genes were analyzed. A total of 142/334 isolates (42.2%) were suspected of carbapenemase production, i.e., intermediate or resistant to ertapenem (ETP) and/or meropenem (MEM) and/or imipenem (IPM) according to EUCAST clinical breakpoints (CBPs). A group of 193/334 isolates (57.8%) showing susceptibility to ETP, MEM, and IPM was considered the negative-control group in this study. CLSI and EUCAST carbapenem CBPs and the new EUCAST MEM screening cutoff were evaluated as screening parameters. ETP, MEM, and IPM with or without aminophenylboronic acid (APBA) or EDTA combined-disk tests (CDTs) and the Carba NP-II test were evaluated as confirmation assays. EUCAST temocillin cutoffs were evaluated for OXA-48 detection. The EUCAST MEM screening cutoff (<25 mm) showed a sensitivity of 100%. The ETP APBA CDT on Mueller-Hinton agar containing cloxacillin (MH-CLX) displayed 100% sensitivity and specificity for class A carbapenemase confirmation. ETP and MEM EDTA CDTs showed 100% sensitivity and specificity for class B carbapenemases. Temocillin zone diameters/MIC testing on MH-CLX was highly specific for OXA-48 producers. The overall sensitivity, specificity, positive predictive value, and negative predictive value of the Carba NP-II test were 78.9, 100, 100, and 98.7%, respectively. Combining the EUCAST MEM carbapenemase screening cutoff (<25 mm), ETP (or MEM), APBA, and EDTA CDTs, and temocillin disk diffusion on MH-CLX promises excellent performance for carbapenemase detection.